Effectiveness of the AUDIT-C as a Screening Test for Alcohol Misuse in Three Race/Ethnic Groups - Frank, Danielle (Springer-Verlag, 2008)
BACKGROUND: The Alcohol Use Disorders Identification Test—Consumption (AUDIT-C) is a brief validated screen for risky drinking and alcohol abuse and dependence (alcohol misuse). However, the AUDIT-C was validated in predominantly White populations, and its performance in different racial/ethnic groups is unclear. OBJECTIVE: To evaluate the validity of the AUDIT-C among primary care patients from the predominant racial/ethnic subgroups within the United States: White, African American, and Hispanic. DESIGN: Cross-sectional interview validation study. PARTICIPANTS: 1,292 outpatients from an academic family practice clinic in Texas (90% of randomly sampled eligible). MEASUREMENTS AND MAIN RESULTS: Race/ethnicity was self-reported. Areas under the receiver operating curve (AuROCs) evaluated overall AUDIT-C performance in the 3 racial/ethnic groups compared to diagnostic interviews for alcohol misuse. AUDIT-C sensitivities and specificities at recommended screening thresholds were compared across racial/ethnic groups. AuROCs were greater than 0.85 in all 3 groups, with no significant differences across racial/ethnic groups in men (P = .43) or women (P = .12). At previously recommended cut points, there were statistically significant differences by race in AUDIT-C sensitivities but not specificities. In women, the sensitivity was higher in Hispanic (85%) than in African-American (67%; P = .03) or White (70%; P = .04) women. In men, the sensitivity was higher in White (95%) than in African-American men (76%; P = .01), with no significant difference from Hispanic men (85%; P = .11). CONCLUSIONS: The overall performance of the AUDIT-C was excellent in all 3 racial/ethnic groups as reflected by high AuROCs. At recommended cut points, there were significant differences in the AUDIT-C’s sensitivity but not in specificity across the 3 racial/ethnic groups. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi: 10.1007/s11606-008-0594-0) contains supplementary material, which is available to authorized users.